Survey on Computer Forensics and its most using Technique Steganography - Thangavel, Vijayakumar (Recent Research Reviews Journal, 2023)
A subfield of digital forensic science called computer forensics deals with evidence discovered on computers and digital storage devices. Computer forensics aims to detect, preserve, retrieve, analyse and communicate facts and views regarding the digital information by performing a forensically sound examination of digital media. The purpose of this study is to provide a brief discussion of computer forensics and related methods. Steganography is one of the most widely utilised of these approaches, and it will also be briefly discussed below.